Penerapan Metode Studi Kasus Dalam Penelitian Kualitatif - Ilhami, Muhammad Wahyu; Nurfajriani, Wiyanda Vera; Mahendra, Arivan; Sirodj, Rusdy Abdullah; Afgani, Muhammad Win (Jurnal Ilmiah Wahana Pendidikan, 2024)
Case studies as part of the research method provide a certain framework for the stages of the process, including determining the theme and subject of research, determining the place, determining accurate methods, determining relevant data collection techniques, analyzing the results of data obtained from research subjects, making conclusions and research reports. The findings can be said to be scientific if they meet objective, systematic standards and follow scientific procedures. Library research is the type of research used in this study. Library research is also often referred to as literature review, which is a series of activities related to how to collect library data by looking for literature that discusses and uses the case study method in its research. Some research methods that are often used to reveal a case in the social field, one of which is the case study method. Case studies become a research method that provides an in-depth contribution in revealing certain problems or cases, whether the scope of individuals, groups or organizations. Case studies become useful when a person/researcher wants to understand a particular problem or situation very deeply and where people can identify cases that are rich in information, rich in the sense that a big problem can be studied from several examples of phenomena and usually in the form of questions.